2016
DOI: 10.1021/acs.iecr.6b02028
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Gas Distributor on Hydrodynamics and the Rochow Reaction in a Fluidized Bed Membrane Reactor

Abstract: Gas distributor configurations were optimized for the direct synthesis of methychlorosilanes in a fluidized bed membrane reactor. The Syamlal−O'Brien drag model was optimized to allow reasonable prediction of solid volume fraction, and the influences of opening area ratio and the number of holes of gas distributor on hydrodynamics were investigated by computational fluid dynamics simulation. The results indicated that a gas distributor with a 0.53% opening area ratio and 19 holes exhibited a steadier radial so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…Zhang et al suggested that the optimized Syamlal-O'Brien drag model can reasonably predict hydrodynamic behavior in the fluidized bed membrane reactor, and the computational fluid dynamics simulation results showed good agreement with the experimental data (Figure 10a). [53] The effects of gas distributor configuration on Rochow-Müller process were also tested experimentally, and M2 selectivity and Si conversion were both increased, as shown in Figure 10b.…”
Section: Reactor Optimizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Zhang et al suggested that the optimized Syamlal-O'Brien drag model can reasonably predict hydrodynamic behavior in the fluidized bed membrane reactor, and the computational fluid dynamics simulation results showed good agreement with the experimental data (Figure 10a). [53] The effects of gas distributor configuration on Rochow-Müller process were also tested experimentally, and M2 selectivity and Si conversion were both increased, as shown in Figure 10b.…”
Section: Reactor Optimizationmentioning
confidence: 99%
“…(a); Effects of gas distributor configurations on M2 yield (b). Reprinted with permission . Copyright 2016 American Chemical Society.…”
Section: Chemistry: State‐of‐the‐artmentioning
confidence: 99%
“…Solid volume fraction and M2 (DMDC) selectivity in a lab-scale FBR with different distributor configurations: left, solid volume fraction; right, M2 selectivity. Reprinted with permission from ref . Copyright 2016 American Chemical Society.…”
Section: Reactor Design For M2 Productionmentioning
confidence: 99%
“…A gas distributor strongly affects the gas distribution and solid fluidization quality in a fluidized bed reactor. Zhang et al 91 developed a 3D computational model to simulate MCS synthesis in an FBR and investigated the effects of the ratio of open area and holes number of the gas distributor on the gas−solid flow, M2 selectivity, and silicon conversion in the reactor. Authors found that a gas distributor with 0.53% opening ratio and 19 holes showed a steadier radial solid-volume-fraction-distribution and a smaller dead-zonearea.…”
Section: Gas Distributormentioning
confidence: 99%